Pengembangan Ekosistem Talenta Sumber Daya Manusia Lokal untuk Mendorong Kemajuan Sosial dan Kemandirian Ekonomi Masyarakat: Studi Kuliah Pengabdian Masyarakat di Kampung Melayu, Batam - Isnandar Syahputra; Angga Pramadani; Anindah Aestisyah; Shasya Chorollina; Salsabilah Febriamin; Mita Panggabean; Gendis Triayu Vionita; Putri Salsabila Ellisa; Salsalivia Hardi; Anggie Dellya; Delmita Sari; Robby Kurniawan; Nurmayunita Nurmayunita (CV. ALIM'SPUBLISHING, 2026)
This community service program was conducted by Kelompok 4 Regu B in Kampung Melayu, Kelurahan Batu Besar, Kecamatan Nongsa, Batam, with the theme of developing a local human resource talent ecosystem for social progress and economic independence. The program implemented two work activities through a participatory assistance approach consisting of observation, understanding, planning, action, and reflection stages. The first activity focused on branding and promotional assistance for two home-based micro enterprises, namely a breakfast stall and a concrete-roster business, through logo creation, promotional banners, menu and catalogue design, and digital map registration. The second activity involved door-to-door education on digital and household financial literacy, along with the distribution of organic and non-organic waste bins as appropriate technology support. The results indicate that both enterprises achieved clearer brand identities and more attractive promotional media, while residents demonstrated improved digital awareness and better household financial management practices through income, expense, and savings records. These findings show that local talent ecosystem development requires two complementary strategies: strengthening micro-enterprise identity and market access, as well as improving household digital and financial literacy through active community participation.